Klinckowstroemia multisetillosa Rosario & Hunter (Acarina: Trigynaspida: Klinckowstroemiidae) associated with three species of Proculus Kuwert (Coleoptera: Passalidae) - Padilla, Elcidia Emely; Schuster, Jack (Instituto de Ecología, A.C., 1994)
Klinckowstroemia multisetillosa Rosario & Hunter was known to be asociated with Proculus mniszechi Kaup in Guatemala. We have found K. multisetillosa associated with allopatric populations of P. burmeisteri Kuwert and P. opacipennis (Thonipson). K. multsietillosa is now known from 4 regions of Guatemala and 1 of Honduras. At prosent, there appears to be no gene flow between these 5 areas. Only 1 species of Proculus is known from each región. Since this genus is flightless, the distribution of mites among these "geografic islands" could be explained in 2 ways: the first implies a possible wide spread ancient distribution and the second implies the distribution of such mites by phoresy on other passalid specics that fiy.